Hydrodeoxygenation of stearic acid using Mo modified Ni and Co/alumina catalysts: Effect of calcination temperature. Issue 7 (2nd July 2020) - Kumar, Pankaj; Maity, Sunil K.; Shee, Debaprasad
Abstract: The calcination temperature (Cal-Temp) plays a vital role in the performance of supported metal catalysts. In this work, the alumina supported Ni, NiMo, Co, and CoMo catalysts were prepared at different Cal-Temp. The catalysts were characterized by various techniques to identify the catalytically active different surface species to correlate their role in the hydrodeoxygenation of stearic acid. With increasing Cal-Temp, the metal dispersion was increased for Ni, NiMo, and CoMo catalyst (up to 973 K) and decreased for Co catalyst. With increasing Cal-Temp, the catalytic activity was thus increased for Ni and NiMo catalyst and decreased for Co catalyst. The activity of CoMo catalyst was, however, enhanced with rising Cal-Temp up to 973 K and declined slightly after that. The optimum Cal-Temp for Ni, NiMo, Co, and CoMo catalyst was found to be 1023 K, 973 K, 773 K, and 973 K. The reaction followed the decarbonylation route over active metallic centers (Ni and Co) and the HDO route over oxophilic M 2+ ⋅MoO2 (M = Ni/Co) and reducible cobalt oxide species. The C17 alkane was thus the principal product over Ni catalyst, whereas C18 alkane was the primary product over CoMo and NiMo catalyst. In contrast, both C17 and C18 alkanes were significant over Co catalyst.